Typologies: what types of foreign executives are appointed by local organisations and what types of organisations appoint them? - Arp, Frithjof (Rainer Hampp Verlag, 2013)
Current issues in international human resource management include global careers that differ from traditional expatriate assignments. A number of foreign executives have in recent years been appointed to positions in the headquarter operations of culturally distant organisations. These appointments of foreign executives in local organisations (FELOs) can be viewed as a specific form of self-initiated expatriation (SIE), with several distinct types of FELOs found in fieldwork studies. This article offers typologies of the individuals and organisations involved in the FELO phenomenon. These typologies elucidate that FELO appointments do not necessarily indicate a geocentric hiring approach, and assist in identifying which FELO workplaces produce successful outcomes as well as those which are likely to fail. The applicability to other country contexts, implications for theory on diversity in management teams, and key criteria for FELO hiring practices are discussed.